The function of metal–organic frameworks in the application of MOF-based composites. Issue 7 (4th June 2020) - Chen, Luning; Zhang, Xibo; Cheng, Xiqing; Xie, Zhaoxiong; Kuang, Qin; Zheng, Lansun
Abstract : In this review, recent progress in MOF-based composites was summarized with an effort to clarify the structure–performance relationship of MOF-based composites, with particular emphasis on the functions of MOF components for practical applications. Abstract : In the last two decades, metal–organic frameworks (MOFs), as a class of porous crystalline materials formed by organic linkers coordinated-metal ions, have attracted increasing attention due to their unique structures and wide applications. Compared to single components, various well-designed MOF-based composites combining MOFs with other functional materials, such as nanoparticles, quantum dots, natural enzymes and polymers with remarkably enhanced or novel properties have recently been reported. To efficiently and directionally synthesize high-performance MOF-based composites for specific applications, it is vital to understand the structural–functional relationships and role of MOFs. In this review, preparation methods of MOF-based composites are first summarized and then the relationship between the structure and performance is determined. The functions of MOFs in practical use are classified and discussed through various examples, which may help chemists to understand the structural–functional relationship in MOF-based composites from a new perspective.